Pengembangan LKPD untuk Meningkatkan Literasi Sains Peserta Didik Sekolah Dasar - Fitri Handayani; Narhendi; Pramudiyanti; Pramita Sylvia Dewi (Lentera: Jurnal Ilmiah Kependidikan, 2024)
The use of Student Worksheets (LKPD) based on Discovery Learning is an interesting approach in an effort to increase students' scientific literacy. This research aims to explore the effectiveness of Discovery Learning-based LKPD in increasing students' scientific literacy. This research uses the ADDIE research model with research subjects totaling 30 students in class IV UPTD SDN 23 Negeri Katon. This development research has produced Student Worksheets (LKPD) which have been tested through validation and evaluation, and declared "Very Valid" and "Very Appropriate" for use. The LKPD that has been created has gone through a process that is in accordance with the recommendations and benefits according to experts. The research results show that the use of Discovery Learning-based LKPD significantly increases students' understanding of science concepts compared to conventional learning methods. The implication of this research is the importance of integrating Discovery Learning-based LKPD in science learning to increase students' scientific literacy at the elementary school level.